CONCEPT OF GOD, HUMANITY AND INSAN KAMIL: HALL AL-RUMUZ WA MAFATIH AL-KUNUZ MANUSCRIPT OF IBN ‘ARABI - Hajam; Theguh Saumantri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
There are at least two items preserved in the manuscript of Ibn Arabi's Hall Rumuz wa Mafatihu al-Kunuz on the teaching of tasawuf, located in Cirebon Palace, West Java, Indonesia: Hall al-Rumuz (a collection of answers to every query based on the Sufi) and Mafatih al-Kurum (a brief summary of the secret of the teaching of tasawuf). A hermeneutic analysis of the library study highlights two important facets of Ibn Arabi's teaching: first, the knowledge that unlocks the treasure, and second, the possession of the key that enables one to reach the pinnacle of existence (al-Insan al-Kamil). To achieve perfection, one must possess a key as the method of access. Ibn Arabi stresses the significance of accurately comprehending the notions of divinity, humanity, and the road to perfection. This is to ensure that individuals do not forfeit their fitrah or their inherent identity as beings within a highly dynamic social environment.